A comunicação da Igreja Católica na América Latina e Caribe a partir dos documentos conclusivos do CELAM: uma visão compreensiva de suas teorias e de suas práticas - Alvarenga, Ricardo Costa (2021)
This thesis has as its theme the communication of and in the Catholic Church in Latin America and the Caribbean, and, as an object of study, the Concluding Documents of the General Conferences of the Latin American and Caribbean Episcopate (Celam), held in Rio de Janeiro (Brazil, 1955), in Medellín (Colombia, 1968), in Puebla (Mexico, 1979), in Santo Domingo (Dominican Republic, 1992) and in Aparecida (Brazil, 2007). The main objective is to understand the main communication trends of the Catholic Church from the five documents. We work with the hypothesis that it is possible to identify in these documents, at least, three main ways of understanding the phenomenon: 1) communication for social transformation, focused on protagonism and engagement in social issues; 2) communication from an instrumental and mass perspective, at the service of evangelization and promotion of Catholic doctrine; and 3) communication as a practice of building the organizational image. The theoretical framework develops from mostly Latin American authors, from the perspective of Southern Epistemologies (Boaventura de Sousa Santos). Sandra Arenas, Enrique Dussel, Luiz Fernando Medeiros Rodrigues, João Batista Libanio, Pablo Richard, among others, are called upon to understand the nuances of the structure and political and social position occupied by the Catholic Church in this part of the world. Regarding the Church-Communication relationship, we prefer Joana Puntel, Pedro Gilberto Gomes and Benito Spoletini. In an attempt to amplify the understanding about the communication trends raised as a working hypothesis, we resorted to the help of Cicilia Maria Krohling Peruzzo, Jan Servaes, Alfonso Gumucio Dagron, Thomas Tufte, John B. Thompson, Eduardo Neiva, Margarida M. Krohling Kunsch, Gary Kreps. The work path is formed from the theoretical-methodological framework of Depth Hermeneutics (John B. Thompson), in the light of understanding as a method (Dimas A. Künsch). The thesis contributes to a deeper understanding, although not unique and much less definitive, of the ways in which the Catholic Church understands communication, based on the five documents of Celam, and it also presents a broader picture of the people reality that inhabit this part of the planet, with their histories, memory, social and political struggles, from the perspective of social communication.(AU)